2022
DOI: 10.1080/07853890.2022.2044508
|View full text |Cite
|
Sign up to set email alerts
|

Examining knowledge and traditional practices of mothers with children under five in Turkey on diarrhoea according to education levels

Abstract: Background Diarrhoea still ranks among the top causes of the deaths of children under five years old in the world. In solving this important health problem, it is necessary and imperative to know the health-related knowledge levels of mothers who take care of the child individually and the traditional practices they perform when their children are sick, in order to provide effective health education. Aim This study aims to examine the knowledge levels and traditional pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 22 publications
1
6
0
Order By: Relevance
“…In a study conducted in Turkey, it was reported that mean age of mothers was 32.37±4.63 and the 14.4% had completed their primary education while 17.9% had completed their secondary education and 45.9% were graduates. Similarly, they have reported that 40.2% of mothers were housewives 15 . Majority of our study participants, (78.33%), knew about ORT but 21.67% didn't and preferred home based remedies.…”
Section: Discussionmentioning
confidence: 88%
See 1 more Smart Citation
“…In a study conducted in Turkey, it was reported that mean age of mothers was 32.37±4.63 and the 14.4% had completed their primary education while 17.9% had completed their secondary education and 45.9% were graduates. Similarly, they have reported that 40.2% of mothers were housewives 15 . Majority of our study participants, (78.33%), knew about ORT but 21.67% didn't and preferred home based remedies.…”
Section: Discussionmentioning
confidence: 88%
“…Kaçan et al have also reported that the study participants in their study used home based remedies to treat diarrhea in their children. Preferred ones were giving banana, mashed potatoes or porridge 15 . Different other studies also reported that a wide variety of home remedies were used by mothers/care-givers for treating diarrhea such as sugar-salt mix for drinking, breast feeding, drinking rice water or fruit juice, using soups, yogurt or mashed potatoes 15,16,17 .…”
Section: Discussionmentioning
confidence: 99%
“…Education can raise awareness of mothers' risks of diarrhea in children and its impact on their health. This awareness can motivate mothers to pay more attention to hygiene practices, nutrition, and other factors that can affect diarrhea prevention (Yüksel Kaçan, Palloş and Özkaya, 2022). Education provides more in-depth information about the causes of diarrhea in terms of bacterial, viral, and environmental factors.…”
Section: Discussionmentioning
confidence: 99%
“…Most mothers preferred to feed their children with banana during diarrhoea (92.5%) (Kaçan et al, 2022).…”
Section: Discussionmentioning
confidence: 99%
“…In another study, the knowledge score of participating mothers was high. Most mothers preferred to feed their children with banana during diarrhoea (92.5%) (Kaçan et al, 2022).…”
Section: Discussionmentioning
confidence: 99%